1998
DOI: 10.1152/jappl.1998.84.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Effects of voluntary activity and genetic selection on aerobic capacity in house mice (Mus domesticus)

Abstract: . Effects of voluntary activity and genetic selection on aerobic capacity in house mice (Mus domesticus). J. Appl. Physiol. 84(1): 69-76, 1998.-An animal model was developed to study effects on components of exercise physiology of both ''nature'' (10 generations of genetic selection for high voluntary activity on running wheels) and ''nurture'' (7-8 wk of access or no access to running wheels, beginning at weaning). At the end of the experiment, mice from both wheel-access groups were significantly lighter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
204
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 194 publications
(235 citation statements)
references
References 27 publications
28
204
3
Order By: Relevance
“…Lower body mass in HR lines has been a consistent finding in the selection experiment since generation 14 (13.6% smaller at 79days old) (Swallow et al, 1999), and a trend for reduced body mass was observed at generation 10 (e.g. Swallow et al, 1998b). The difference in body mass between HR and C lines makes it important to include body mass as a covariate in statistical comparisons of organ size, including brain mass and volume (see Tables2, 3).…”
Section: Discussionmentioning
confidence: 56%
“…Lower body mass in HR lines has been a consistent finding in the selection experiment since generation 14 (13.6% smaller at 79days old) (Swallow et al, 1999), and a trend for reduced body mass was observed at generation 10 (e.g. Swallow et al, 1998b). The difference in body mass between HR and C lines makes it important to include body mass as a covariate in statistical comparisons of organ size, including brain mass and volume (see Tables2, 3).…”
Section: Discussionmentioning
confidence: 56%
“…In brief, after a 1-wk vivarium acclimation, the mice were oriented twice to running in a small cell suspended above a human treadmill. A shock grid was mounted at the rear of the cell (1.5 mA, 150 V) to provide stimulus for the animals to run (35). During testing, each mouse was placed in the treadmill cell and allowed 3 min of rest.…”
Section: Estimation Of Exercise Endurancementioning
confidence: 99%
“…Application of systemic hormones in varying doses and at varying times in development, followed by measurement of impacts on trait development, would provide an assessment of trait interdependence. Estimates of heritability and of environmental effects on trait expression, as well as artificial selection on one or another member of a complex, would reveal the potential for correlated or independent response in the other traits (e.g., Sefton and Siegel 1975;Cunningham and Siegel 1978;Garland 1988;Siegel and Dunnington 1990;Bakker 1994;Zera and Zhang 1995;Van Tienderen and Van Hinsberg 1996;Swallow et al 1998).…”
Section: Applying the Adaptation/exaptation Distinction To Hormonal Tmentioning
confidence: 99%